Vulnerable older people’s views on proactive care planning: a qualitative interview study in primary care - Lisa Kastbom; Anna Olaison; Annette Sverker; Anna Segernäs (BJGP Open)
Background: Patients in old age often have complex care needs owing to multimorbidity and polypharmacy. This qualitative study is part of a larger ongoing Swedish intervention trial Secure And Focused primary care for older pEople (SAFE), including shorter care agreements based on person-centred patient goals. Aim: To explore, in a primary care setting, the views of older and vulnerable patients on a more systematic, proactive approach to care planning, including establishing and documenting care agreements based on person-centred goals. Design & setting: Individual semi-structured interviews with patients (n = 25) aged >75 years from 12 intervention primary healthcare centres in two counties in Sweden. Method: Interviews were conducted between June and October 2023. They were digitally recorded and transcribed verbatim. Latent qualitative content analysis was used. Results: The following three categories, with 10 sub-categories, were found: I would like to live in the present, so why plan ahead? Let me decide versus they know best; and Care agreements usually went unnoticed. The latent theme — The ambivalence of care planning in the fourth age — was created to give a deeper meaning to the content of the categories. Conclusion: This study emphasises that older, vulnerable persons have varying attitudes towards participation in proactive care planning. This ambivalence may originate from the individual’s desire to have their autonomy respected and express future care preferences on the one hand, and to avoid or postpone end-of-life conversations and care planning on the other hand. Patients also expressed a desire to be more actively involved in care planning. Although care agreements have the potential to increase patient involvement in proactive care planning, they often went unnoticed. The conversation itself was essential.